Serum Level Of Dehydroepiandrosterone Sulphate Hormone at Various Acne Vulgaris Severity - Windy Miryana; Mohammad Cholis; Aunur Rofiq; Tantari Sugiman (Faculty of Medicine, Universitas Airlangga, 2014)
Background: The pathogenesis of acne vulgaris (AV) is multifactorial. Hormone dehydroepiandrosterone sulfate (DHEAS) is an androgen hormone important in the initial formation of AV in women, namely the development and differentiation of sebaceous glands, which are mostly found in human blood serum. Research looking at differences in hormone levels in serum DHEAS between various degrees of severity of AV in women has not been done. Purpose: To measure whether there was a difference of serum level of DHEAS hormone at various AV severity in women. Methods: The study design was a cross-sectional analytic observational, with ninety subjects, women, by using inclusion and exclusion criterias. The diagnosis was based on clinical examination. AV severity was categorized into 3 groups, mild, moderate, and severe, that based on Combined Acne Severity Index by Lehmann. Serum level of DHEAS hormone was measured with ELISA method. The difference of serum level of DHEAS hormone at various AV severity was analyzed with non-parametric statistical test Kruskal-Wallis and Mann-Whitney. Results: The mean serum level of DHEAS hormone in women with mild AV is 1076.01±257.89 pg/ml, in moderate AV is 1971.95±272.73 pg/ml, and in severe AV is 19678.22±33536.38 pg/ml. Conclusion: There were significant difference of serum level of DHEAS hormone between women with mild and moderate AV, mild and severe AV, and moderate and severe AV (p value < 0.05), but still below from normal level.Key words: acne vulgaris, women, observasional analytic, serum level DHEAS, severity grading.